Fires in hospital buildings: knowledge held by nursing professionals regarding prevention, combat and escape - Renato Santiago Costa Rodrigues; Ana Elisa Bauer de Camargo Silva; Lizete Malagoni de Almeida Cavalcante Oliveira; Virginia Visconde Brasil; Katarinne Lima Moraes; Jacqueline Andréia Bernardes Leão Cordeiro (Universidade Federal de Goias, 2014)
This study analyzes the knowledge and conduct of nursing professionals regarding hospital fire prevention, combat and escape. A descriptive study conducted in a public teaching hospital in Goiânia/GO, Brazil, with 109 nursing professionals. Data was collected in 2011 using structured interviews with questionnaires, and descriptive statistics for analysis. Most subjects were female, nursing technicians/assistants (67.9%), knew the Fire Department's number (85.3%) and the extinguisher's location (80.7%), but ignored how they functioned (69.7%). Also, 57.8% of interviewees ignored the exit routes and, in case of fire, would alert the fire department, guide people towards the exit, use the extinguisher or jump out of the windows. The gaps identified in this study indicate that in order to guarantee adequate conduct, fire training is necessary, as is the establishment of escape routes, since technological resources are useless without individuals who can act preventively. Risk reduction implies in institutional safety and quality. doi: 10.5216/ree.v16i2.25054